2014
DOI: 10.5539/ijps.v6n3p106
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Attachment Styles on the Relationship of Alexithymia and Fear of Intimacy with Marital Satisfaction

Abstract: Attachment styles, alexithymia, and fear of intimacy are considered to be detrimental to degree of satisfaction within the couples relationships. The present study aimed to investigate the moderating role of attachment styles on the relationship of alexithymia and fear of intimacy with marital satisfaction in a sample of Iranian students. Participants (313 males, 375 females) filled the Adult Attachment Inventory (AAI), the Farsi version of the Toronto Alexithymia Scale-20 (FTAS-20), Fear of Intimacy Scale (FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 54 publications
12
23
0
Order By: Relevance
“…The present results thus reinforce the notion that alexithymia and dissociation are positively associated with the fear of intimacy, which in turn may account, at least in part, for the reported association between high levels of alexithymia and insecure attachment ( Thorberg et al, 2011 ). Present findings are also consistent with the research by Montebarocci et al (2004) and Besharat et al (2014b) who showed positive relationships of TAS-20 alexithymia with the fear of intimacy, as well as insecure attachment and marital dissatisfaction ( Besharat et al, 2014a ). The consistent finding of a strong association between alexithymia, dissociation and the fear of intimacy suggests that targeting the latter to improve interpersonal functioning may be a viable approach in the treatment of clients suffering from depression, anxiety, or substance disorders, who also exhibit high levels of alexithymia.…”
Section: Discussionsupporting
confidence: 92%
“…The present results thus reinforce the notion that alexithymia and dissociation are positively associated with the fear of intimacy, which in turn may account, at least in part, for the reported association between high levels of alexithymia and insecure attachment ( Thorberg et al, 2011 ). Present findings are also consistent with the research by Montebarocci et al (2004) and Besharat et al (2014b) who showed positive relationships of TAS-20 alexithymia with the fear of intimacy, as well as insecure attachment and marital dissatisfaction ( Besharat et al, 2014a ). The consistent finding of a strong association between alexithymia, dissociation and the fear of intimacy suggests that targeting the latter to improve interpersonal functioning may be a viable approach in the treatment of clients suffering from depression, anxiety, or substance disorders, who also exhibit high levels of alexithymia.…”
Section: Discussionsupporting
confidence: 92%
“…The present results thus reinforce the notion that alexithymia is positively associated with fear of intimacy, which in turn may account at least in part for the reported association between high levels of alexithymia and insecure attachment Troisi et al, 2001). Present findings are also consistent with those of research by Montebaroccia et al (2004) and Besharat et al (2014) which showed positive relationships of TAS-20 alexithymia with fear of intimacy (as indexed by the FIS) as well as insecure attachment and (in the latter study) marital dissatisfaction. Further, a recent study by Doina and Ioana (2015), using the TAS-20 index of alexithymia but a different measure of attachment style than that used in the present study, found a negative relationship of alexithymia with secure attachment but positive relationships with both fearful and preoccupied attachment styles.…”
Section: Discussionsupporting
confidence: 91%
“…The present results thus reinforce the notion that alexithymia is positively associated with fear of intimacy, which in turn may account at least in part for the reported association between high levels of alexithymia and insecure attachment (Thorberg, Young, Sullivan, Lyvers et al, 2011;Troisi et al, 2001). Present findings are also consistent with those of research by Montebaroccia et al (2004) and Besharat et al (2014) which showed positive relationships of TAS-20 alexithymia with fear of intimacy (as indexed by the FIS) as well as insecure attachment and (in the latter study) marital dissatisfaction. Further, a recent study by Doina and Ioana (2015), using the TAS-20 index of alexithymia but a different measure of attachment style than that used in the present study, found a negative relationship of alexithymia with secure attachment but positive relationships with both fearful and preoccupied attachment styles.…”
Section: Discussionsupporting
confidence: 93%